2017
DOI: 10.4236/aim.2017.711060
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Acetic Acid Production Rate by Thermotolerant <i>Acetobacter</i> spp.

Abstract: Thermotolerant microorganisms were collected, identified and characterized under different physiological conditions from various rotten fruits in Bangladesh for vinegar production. Among the 15-isolates characterized previously, the strains F-1, F-3 and F-10 represented Staphylococcus, Bacillus and Acetobacter spp., respectively. After checking various parameters for growth, acetic acid production rate was optimized further. Among the 3-starins analyzed here, the strain F-10 gave maximum acetic acid (7.0 g/100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…In addition, this study concurred with the findings of [26] and [27] in whose report archived the presence of B. cereus, B. thuriengiensis and B. anthracis from raw milk tests. This finding is also in line with [24,28] who reported the nearness of Bacillus sp. F-3 (KF668639) from fruits as a potential maker of acetic acid or its subsidiaries.…”
Section: Bioinformatics Studies Of Aab Isolatessupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, this study concurred with the findings of [26] and [27] in whose report archived the presence of B. cereus, B. thuriengiensis and B. anthracis from raw milk tests. This finding is also in line with [24,28] who reported the nearness of Bacillus sp. F-3 (KF668639) from fruits as a potential maker of acetic acid or its subsidiaries.…”
Section: Bioinformatics Studies Of Aab Isolatessupporting
confidence: 92%
“…The results from titrimetric examination revealed that they are fit for the production of acetic acid where Acetobacter had 3.6g/100ml and Gluconobacter had 1.8g/100ml. [24] in his report revealed that Acetobacter sp. produced least amount of acetic acid (7.0g/100ml) in the presence of 2% ethanol in the medium which was higher than the findings of this study.…”
Section: Bioinformatics Studies Of Aab Isolatesmentioning
confidence: 99%
“…Optimization of fermentation conditions is a key process in fermentation research, along with the selection of the fermentation strain to stimulate metabolic activity and bioactive compound productivity. For acetic acid fermentation, the key factors have been intensively used in the research of fermentation process optimization [ 50 , 51 , 52 , 65 , 66 , 67 ]. Based on the present and previous studies, the optimized fermentation conditions vary widely even when the same species (but different strains) of Acetobacter are used.…”
Section: Discussionmentioning
confidence: 99%
“…Motility was observed by the hanging drop method. Standard biochemical tests generally used to identify AAB such as production of catalase and oxidase, nitrate reduction, and Voges Proskauer's test was performed [13]. The utilization of various carbohydrates such as glucose, trehalose, malonate, arabinose, mannitol, citrate, sucrose, and arginine was also studied.…”
Section: Microscopic and Biochemical Characterization Of Yeast And Aamentioning
confidence: 99%